The Influence of Tafsir Tarbawi in the Formation of Religious Character in Schools - Nana Supriatna; Iskandar Mirza (Classroom: Journal of Islamic Education, 2025)
This study aims to examine the influence of Tafsir Tarbawi in shaping religious character in schools. Tafsir Tarbawi, as an interpretative approach that integrates character education values with the understanding of the Qur’an, is believed to play a significant role in shaping students re;igious. Using qualitative approach, this research involves literature analysis and in-depth interviews with religious teachers, school principals, and students in several schools that implement the Tafsir Tarbawi method in their religious education processes. The research findings indicate that Tafsir Tarbawi significantly contributes to the formation of students religious character. This approach not only teaches the understanding of Qur’anic texts but also instills the moral and ethical values contained within religious teachings. The implementation of Tafsir Tarbawi in schools not only enhances students religious knowledge but also strengthens their religious behaviors, including discipline, empathy, and social responsibility. Furthermore, Tafsir Tarbawi facilitates students in understanding the relationship between religious teachings and daily life, encouraging them to apply religious principles in practical actions. The study also identifies several challenges in the application of Tafsir Tarbawi, such as a lack of resources and training for educators, as well as resistance to changes in traditional teaching methods. Thus, the conclusion of this study is that Tafsir Tarbawi holds great potential for strengthening the formation of students religious continous efforts to enhance teachers capacities and provide adequate resources. It is hoped that the findings of this research can contribute to the development of religion-based character education in Indonesia, particularly in the context of Qur’anic studies in schools.